Sub-Pixel Resolution by Die to Database Reticle Inspection - Avakaw, S. M. (Elektronika ir Elektrotechnika, 2007)
The description of the new Virtual Scanning Algorithms (VSA), providing sub-pixel resolution, is presented. VSA are developed specially for EМ-6029B and EM-6329 die-to-database reticle and photomask inspection systems of UE"KBTEM-OMO" Minsk, Belarus. For the effective building of these algorithms into the inspection system the special two-level dynamic model of optical image was created. This model allows to perform the precise alignment of optical image (collected from the reticle) with a reference image (generated from the design data), and to perform the analysis of optical image to get optimum mutual position of the digitization grid of the inspection system and detected defects position. VSA calculate the second level of this model. Both the VSA and the second level of dynamic model of optical image are presented the Virtual Scanning sub-System (VSS). VSS allows to increase the detection capability of automatic reticle inspection system by means of achievement sub-pixel resolution. During detection of semi-transparent defects, VSA allow to get maximum available amplitude contrast of the CCD-signals on the image model. VSA allow also the inspection system to work without using maximum sensitivity settings with the same detection capability. Result is the reduction of the risk of false or nuisance defects detection while keeping maximum sensitivity to printable defects. The VSS design and test results are discussed. Ill. 3, bibl. 5 (in English; summaries in English, Russian and Lithuanian).